Unconventional protein secretion (UPS) pathways in plants - Ding, Yu; Robinson, David G.; Jiang, Liwen (Current opinion in cell biology, 2014)
As in yeast and mammalian cells, novel unconventional protein secretion (UPS) or unconventional membrane trafficking pathways are now known to operate in plants. UPS in plants is generally associated with stress conditions such as pathogen attack, but little is known about its underlying mechanism and function. Here, we present an update on the current knowledge of UPS in the plants in terms of its transport pathways, possible functions and its relationship to autophagy.